Breaking the Badge: How Burnout and Compensation Shape Police Performance Through Job Satisfaction: Mengurai Masalah: Bagaimana Kelelahan dan Kompensasi Mempengaruhi Kinerja Polisi Melalui Kepuasan Kerja - Riyanto Setiawan Suharsono; Yogie Indra Yafie; Budi Santoso; Trias Setyowati (Universitas Muhammadiyah Sidoarjo, 2025)
This study investigates the effects of burnout and compensation on the job performance of personnel in the Surabaya Regional Police, with job satisfaction serving as a mediating variable. Using an explanatory research design and Structural Equation Modeling (SEM), data were analyzed from 84 respondents selected from a population of 518 officers using the Slovin formula. The findings reveal that lower levels of burnout and higher compensation significantly improve job performance, both directly and indirectly through increased job satisfaction. Specifically, reduced burnout enhances job satisfaction, which in turn boosts performance, while higher compensation not only increases satisfaction but also strengthens organizational citizenship behavior, further contributing to better performance. These results highlight the importance of addressing employee well-being and fair compensation in law enforcement organizations to enhance satisfaction and operational effectiveness. This research provides practical insights for human resource management in public security sectors aiming to improve workforce productivity and morale.